Cara Kerja dan Penggunaan Motor Direct Current (DC) - Syamsuar, Sayuti; Wibawaningrum, Rizki; Makarim, Hariyanti (Warta Penelitian Perhubungan, 2011)
The motor DC is an electromagnetic process on the mechanical and electrical work that the system will be changed the electrical energy as input to the mechanical energy as output response. The Flemming left hand rule to electromagnet field and the current directions have been indicated of the rotor rotation due the speed of marine vehicle. Ward Leonard Rectifier as generator excitation controls the power system on the submarine. We shown on this paper about mini model SOTO NG, BPPT and others example to known the application in the field.Keywords: motor DC, electromagnetism, Flemming, piston tank, submarine.